ChemInform Abstract: Diastereoselective Synthesis of Biologically Active Cyclopenta[b]indoles. Issue 51 (5th December 2016) - Santos, Marilia S.; Fernandes, Daniara C.; Rodrigues, Manoel T.; Regiani, Thais; Andricopulo, Adriano D.; Ruiz, Ana Lucia T. G.; Vendramini‐Costa, Debora B.; de Carvalho, Joao E.; Eberlin, Marcos N.; Coelho, Fernando
Abstract: Compound (XI) shows promising antiproliferative activity against human tumor cell lines.